Photometry and spectroscopy of the new sdBV CS 1246 - Barlow, B; Dunlap, B; Clemens, J; Lynas-Gray, A; Ivarsen, K; LaCluyze, A; Reichart, D; Haislip, J; Nysewander, M (2010)
We report the discovery of a large-amplitude oscillation in the hot subdwarf B star CS 1246 and present multicolour photometry and time-resolved spectroscopy supporting this discovery.We used the 0.41-m Panchromatic Robotic Optical Monitoring and Polarimetry Telescopes array to acquire data in the u', g', r' and i' filters simultaneously over three consecutive nights in 2009 April. These data reveal a single oscillation mode with a period of 371.707 ± 0.002 s and an amplitude dependent upon wavelength, with a value of 34.5 ± 1.6 mma in the u' filter. We detected no additional frequencies in any of the light curves. Subsequently, we used the 4.1-m SOAR telescope to acquire a time-series of 248 low-resolution spectra spanning 6 h to look for line profile variations. Models fits to the spectra give mean atmospheric values of T eff = 28 450 ± 700K and log g = 5.46 ± 0.11 undergoing variations with semi-amplitudes of 507 ± 55K and 0.034 ± 0.009, respectively. We also detect a radial velocity oscillation with an amplitude of 8.8 ± 1.1 kms-1. The relationship between the angular and physical radii variations shows that the oscillation is consistent with a radial mode. Under the assumption of a radial pulsation, we compute the stellar distance, radius and mass as d = 460 ± 19090 pc, R = 0.19 ± 0.08 R⊙ and M = 0.39 ± 0.300.13M⊙, respectively, using the Baade-Wesselink method. © 2010 The Authors. Journal compilation © 2010 RAS.